Digitalizing a Fuzzy Observer-Based Output-Feedback Control Intelligent Digital Redesign Approach. - Ho Jae Lee
This paper concerns an intelligent digital redesign (IDR) technique for a Takagi-Sugeno fuzzy observer-based output-feedback control (FOBOFC) system. The term IDR involves converting an existing analog control into an equivalent digital counterpart in the sense of state-matching. The IDR problem is herein viewed as a minimization problem of the norm distances between nonlinearly interpolated linear operators to be matched. Its constructive condition with global rather than local state-matching is formulated in terms of bilinear matrix inequalities. The main features of the proposed method are that the state estimation error in the plant dynamics is considered in the IDR condition that plays a crucial role in the performance improvement; the stability property is preserved by the proposed IDR algorithm; the separation principle is shown when the premise variables are measurable; finally, the IDR condition for a more general FOBOFC-an estimated premise variable case is conducted. A numerical example is demonstrated to visualize the feasibility of the developed methodology
Keywords: Takagi-Sugeno system; Bilinear matrix inequalities; Fuzzy observer; Intelligent digital redesign; Nonlinearly interpolated linear operators; Output feedback control; Stability property; State estimation error; State matching